PENINGKATAN AKTIVITAS BELAJAR SISWA DENGAN MODEL PEMBELAJARAN PICTURE AND PICTURE PADA PELAJARAN SENI BUDAYA - Rosmalem . (JURNAL HANDAYANI PGSD FIP UNIMED, 2016)
Abstract: Improvement of student learning activities with learning model picture and picture on the lesson of art and culture. The study aims to look at the students' learning activities that include learning activities of students subjects Arts Culture and student achievement by using model picture and picture. The research subject classes IX-4 SMP Negeri 1 Namorambe totaling 28 students. Cycle I write, read (42%), working LKS (21%), ask peers (11%), ask the teacher (9%), which is not relevant to KBM (17%). Data activity of students in the second cycle observations writing, reading (24%), working LKS (45%), ask peers (20%), ask the teacher (6%), which is not relevant to KBM (5%). Increased student learning outcomes with classical completed by 46.4%, the second cycle of 92.8% due classical. Keywords:Model Picture and Picture,Activities Learning,Learning Outcomes. Abstrak : peningkatan aktivitas belajar siswa dengan model pembelajaran picture and picture pada Pelajaran seni budaya. Penelitian bertujuan untuk melihat aktivitas belajar siswa yang mencakup aktivitas belajar siswa mata pelajaran Seni Budaya dan prestasi belajar siswa dengan menggunakan model pembelajaran picture and picture. Subjek  penelitian kelas IX-4 SMP Negeri 1 Namorambe berjumlah 28 siswa. Siklus I menulis,membaca (42%), mengerjakan LKS (21%), bertanya sesama teman (11%), bertanya kepada guru (9%), yang tidak relevan dengan KBM  (17%). Data aktivitas siswa menurut pengamatan siklus II menulis,membaca (24%),  mengerjakan LKS (45%), bertanya sesama teman (20%), bertanya kepada guru (6%), yang tidak relevan dengan KBM  (5%). Hasil belajar siswa meningkat dengan tuntas klasikal sebesar 46,4%, siklus II tuntas klasikal sebesar 92,8%. Kata Kunci: Model Picture and Picture, Aktivitas Belajar, Hasil Belajar.